LGBTQ Awareness and Allies: Building Capacity in a Bachelor of Education Program - Kearns, Laura-Lee; Mitton-Kukner, Jennifer; Tompkins, Joanne (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
This research describes the impact of an integrated training program (Positive Space I and Positive Space II) on pre-service teachers’ understandings of and abilities to create safe spaces for lesbian, gay, bi-sexual, transgendered, two-spirited, queering and/or questioning (LGBTQ) youth and allies in schools. Our Bachelor of Education program incorporates these workshops as part of sociology of education and inclusion classes that are mandatory courses for all pre-service teachers. Our findings suggest that for the pre-service teachers we teach, the Positive Space program is needed if they are to be allies and to interrupt heteronormativity.